2012
DOI: 10.1002/star.201200168
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties and antioxidant capacity of debranched starch–ferulic acid complexes

Abstract: Amylose, a primarily linear polysaccharide of (1 ! 4)-a-D-glucose units, displays a folding in a helical conformation and has an ability to form an inclusion complex with a variety of ligands. In this study, debranched starch-ferulic acid complexes were produced by adding ferulic acid to the debranched cassava starch paste and their physicochemical properties and antioxidant capacity were investigated. The mixing ratios of ferulic acid to starch were 0.02 (DS-FA0.02), 0.05 (DS-FA0.05), and 0.10 g ferulic acid/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…The ferulic acid in the complex with debranched cassava starch ranged 6.8–31.5 mg g −1 ; the genistein content in the complex with unmodified potato amylose ranged 14–113 mg g −1 . It should be noted that both studies only reported the bioactive compounds in the insoluble complex.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The ferulic acid in the complex with debranched cassava starch ranged 6.8–31.5 mg g −1 ; the genistein content in the complex with unmodified potato amylose ranged 14–113 mg g −1 . It should be noted that both studies only reported the bioactive compounds in the insoluble complex.…”
Section: Resultsmentioning
confidence: 94%
“…Zhang et al studied the complexation of lauric acid with debranched high amylose corn starch (Hylon V), and observed that as the debranching time increased from 0 to 24 h, the X‐ray diffraction pattern of the insoluble complexes shifted from the V‐type to a mixture of B + V‐type. Van Hung et al only observed the B‐type crystalline structure for the insoluble complex of ferulic acid with debranched cassava starch. These results indicate the importance of starch DP and the introduction of substituents on the structure of the resultant complexes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The available studies on the complexation of starch with phenolic compounds have not reported the effect of starch molecular size on the complexation yield . The amylose DP involved in the complexation with fatty acids was suggested to be less than 400 but greater than 20, assuming that starch chains of DP >400 would not form a stable helix, but DP <20 was too short to induce the helical conformation.…”
Section: Resultsmentioning
confidence: 99%
“…The solubility (%) of the complex was performed based on the method of Van Hung with slight modification. The sample (0.5 g, db) was suspended in 50 mL of distilled water at different temperatures (20, 50, 70, and 90 °C), shaked thoroughly for 30 min on a magnetic stirrer and then centrifuged at 1200× g for 10 min.…”
Section: Methodsmentioning
confidence: 99%